The effect of plant density on the yield of sweet potato - Szarvas, Adrienn; Szél Hódi, Margit; Monostori, Tamás (Acta Agraria Debreceniensis, 2019)
A field study was conducted in South-East Hungary during the main cropping season of 2016, 2017 and 2018, with the objective of determining the effect of plant spacing on the productivity of sweet potato. Production technology experiments of four repetitions were set up in a randomized block design on sandy soil. The performed treatments consisted of four variations of plant spacing (row distance x plant-to-plant distance): 80 cm x 20 cm, 80 cm x 30 cm, 100 cm x 20 cm, 100 cm x 30 cm. The plant material was the Hungarian registered sweet potato variety ‘Ásotthalmi-12’. Analysis of variance revealed that planting density significantly affected the average yield of storage roots. The highest yield per plant was achieved with the 100 cm x 30 cm (2016, 2017), as well as with the 80 cm x 30 cm (2018) setups. On hectare level, our results showed that the highest plant density of 62,500 plants ha-1 (80 cm x 20 cm setup) could give the highest yield. Comparing the highest tons ha-1 results to those achieved with the plant spacing setups resulting in the highest yield per plant, the differences can be even 13 or 14 tons at hectare level. This finding underlines the importance of choosing the proper planting density towards the higher end.